Efficacy and safety of glucagon-like peptide 1 agonists for Parkinson's disease: a systematic review and meta-analysis - Luis O. S. Nogueira; Roberto A. S. V. Mazetto; Maria L. R. Defante; Vânio L. J. Antunes; Ocílio Ribeiro Gonçalves; Angela Maria Sandini Corso; Marcus V. Della Coletta; Dayany Leonel Boone; Walderico Silva Machado Filho; Vanderci Borges; Henrique Ballalai Ferraz (Arquivos de Neuro-Psiquiatria)
Background Recent research on Parkinson's disease (PD) therapy has highlighted glucagon-like peptide 1 (GLP-1) agonists as potential therapeutic agents. However, recent randomized controlled trials (RCTs) have shown mixed results regarding the use of this medication.